2003
DOI: 10.1097/01.lab.0000056993.28149.bf
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Response to Peripheral Nerve Injury: The Quantitative Contribution of Resident and Hematogenous Macrophages

Abstract: SUMMARY:Whereas local microglial cells of the CNS rapidly respond to injury, little is known about the functional role of resident macrophages of the peripheral nervous system in nerve pathology. Using bone marrow chimeric rats, we recently identified individual resident endoneurial macrophages that rapidly became activated after nerve injury. However, the extent of local macrophage activation and its quantitative contribution to the total macrophage response is unknown. We now have created chimeric mice by tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
185
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(203 citation statements)
references
References 31 publications
14
185
2
2
Order By: Relevance
“…Previous studies following axotomy of primary afferent sensory nerves has been shown to promote the activation and migration of macrophages within the peripheral nerve (Myers et al, 1996;Tofaris et al, 2002;Abbadie et al, 2003) and associated DRG (Hu & McLachlan, 2002). The increased number of macrophages observed may be due to proliferation of resident macrophages or due to infiltration of hematogeneous macrophages into the DRG (Mueller et al, 2003). Functionally, macrophage activation within the DRG and peripheral nerve following peripheral nerve injury is known to help remove degenerating neuronal debris and myelin as well as contribute to subsequent regeneration (Lu and Richardson 1993, Perry and Brown 1992, Hu and McLachlan 2002.…”
Section: Cellular Alterations In Satellite Cells Macrophages and Schmentioning
confidence: 79%
“…Previous studies following axotomy of primary afferent sensory nerves has been shown to promote the activation and migration of macrophages within the peripheral nerve (Myers et al, 1996;Tofaris et al, 2002;Abbadie et al, 2003) and associated DRG (Hu & McLachlan, 2002). The increased number of macrophages observed may be due to proliferation of resident macrophages or due to infiltration of hematogeneous macrophages into the DRG (Mueller et al, 2003). Functionally, macrophage activation within the DRG and peripheral nerve following peripheral nerve injury is known to help remove degenerating neuronal debris and myelin as well as contribute to subsequent regeneration (Lu and Richardson 1993, Perry and Brown 1992, Hu and McLachlan 2002.…”
Section: Cellular Alterations In Satellite Cells Macrophages and Schmentioning
confidence: 79%
“…Nerve fibers distal to the injury undergo rapid degeneration, with only the sheath remaining to guide regenerative axon sprouting; some retraction of proximal fibers also occurs. At the cellular level, the distal degeneration is dominated by a massive accumulation of macrophages, peaking between days 7 and 14 and then gradually clearing (25). At the molecular level, there is an increase in perineural levels of proinflammatory mediators such as TNF-α, IL-1β, CCL2, and CCL3, even before the expansion of the macrophage population, i.e., at days 1-3 (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…In the periphery, the proinflammatory cytokines IL-1␣ and TNF-␣ released by macrophages contribute to behavioral hypersensitivity after peripheral nerve injury (23)(24)(25). Stimulation of the vagus nerve reduces TNF-␣ production by macrophages in response to bacterial endotoxin in wild-type mice, but not in ␣7 nAChR knockout mice (22).…”
Section: Discussionmentioning
confidence: 99%